Light‐Powered Microrobots: Challenges and Opportunities for Hard and Soft Responsive Microswimmers. (21st April 2021) - Bunea, Ada‐Ioana; Martella, Daniele; Nocentini, Sara; Parmeggiani, Camilla; Taboryski, Rafael; Wiersma, Diederik S.
Abstract : Microrobots In article number 2000256, Ada‐Ioana Bunea and co‐workers provide a critical overview of how microrobots can be manufactured and manipulated using light. The cover image shows blue structures printed in hard polymer and precisely manipulated by optical trapping with focused near‐infrared light, together with orange structures printed using soft, light‐responsive materials, which change shape in response to green light. Cover image drawn by Alexandre Wetzel.